Potentials and Challenges of Existing Plastic Pollutant Biodegradation Using Bacteria in Jakarta Bay - Nurdhy, Syarifatun Nisa (Proceeding International Conference on Science and Engineering, 2020)
Research conducted by Research Center for Marine and Fisheries Product Processing and Biotechnology in the three different locations namely Tarakan, Tanjung Balai Asahan, and Jakarta Bay, has identified that Jakarta Bay had the highest plastic debris concentration among the others. Jakarta Bay is directly connected to Thousand Island National Park sea waters, in which large parts of it are marine conservation area. Thus, plastic pollutants potentially threat Jakarta Bay and Thousand Island National Park abundant biodiversity and underwater marine ecotourism. The tools such as garbage transport barges owned by Special Region of the Capital Jakarta Province are not enough to overcome the existing plastic debris. 21 tons waste end up to Jakarta Bay every day. There should be further research about solving existing plastic waste with other technology than using machine. This literature study aims to review and investigate the potentials and challenges of utilizing bacteria to combat existing marine plastic pollution in Jakarta Bay. Established researches showed that some bacteria strains isolated from plastic debris in some sea waters and sediments around the world are capable of degrading polyethylene (PE), polypropylene (PP), and possibly polystyrene (PS). Unfortunately, reports involving plastic degrading ability of bacteria isolated from plastic wastes in Indonesian sea waters, let alone Jakarta Bay, are hard to find if any. There were only researches about isolated bacterias from Jakarta Bay, which were capable of degrading oil spill. Further research about isolated bacteria from plastic debris of Jakarta Bay, should be established. It can be used to identify bacteria strains or consortia that are able to degrade plastic debris with environmentally friendly byproducts. There will be possibilities that oil spill degrading bacteria isolated from Jakarta Bay can also degrade plastics, as both oil spill and plastics are made up from hydrocarbon chains. A recently published research has revealed that Alvoranicus borkumensis isolated from marine plastic debris in Mediterranean Sea was able to degrade PE, while previously other study has isolated it from Thousand Islands sea waters and found it able to degrade marine oil spill. The expression possibility of DNA (deoxyribonucleic acid) sequence coding extracted from wax worm Galleria mellonella into widespread indigeneous Jakarta Bay bacteria and bacteria isolated from plastic debris in Jakarta Bay, can also be taken into account.